2022
DOI: 10.22270/jddt.v12i2-s.5415
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Ambon Banana Stem (Musa paradisiaca var. sapientum (L)) Ethanol Extract as Moisturizing Sheet Mask

Abstract: Ambon banana stem are known to contain chemical compounds including flavonoids, saponins, and tannins. One of these chemical compounds has the potential as an antioxidant, namely flavonoids which has antioxidant properties as free radical scavengers. Antioxidants can be used to repair skin cells damaged by free radicals, these antioxidants can provide a moisturizing and brightening effect on the skin so that the skin is not only kept moist and looks radiant. The purpose of this study was to formulate sheet mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 10 publications
0
9
0
6
Order By: Relevance
“…If the pH of the body lotion is low, it can irritate the skin, otherwise if the pH of the preparation is too high, it will cause the skin to become dry. The results of the pH test on all lotion formulations showed that they met the standard not less than 4.5 and not more than 6.5 9,12 . Based on research conducted by Angriani Lisa (2019), the pH of the dried extract Clitoria ternatea L. flower was 4-5 which indicated that the extract was acidic.…”
Section: Ph Testmentioning
confidence: 86%
See 2 more Smart Citations
“…If the pH of the body lotion is low, it can irritate the skin, otherwise if the pH of the preparation is too high, it will cause the skin to become dry. The results of the pH test on all lotion formulations showed that they met the standard not less than 4.5 and not more than 6.5 9,12 . Based on research conducted by Angriani Lisa (2019), the pH of the dried extract Clitoria ternatea L. flower was 4-5 which indicated that the extract was acidic.…”
Section: Ph Testmentioning
confidence: 86%
“…The lotion was applied on the back of the volunteer's hand which had been marked every week for 4 weeks. Changes in skin condition were observed and re-measured every week on the skin of volunteers using a skin analyzer to see the increase in skin moisture levels and the results were recorded 10,12 .…”
Section: B Moisture Effectiveness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The organoleptic test is carried out to see the physical appearance of the essence by observing changes in the shape, smell and color of the essence that has been made before and during cycling test 10,11,12 .…”
Section: Organoleptic Testmentioning
confidence: 99%
“…The preparation must show a homogeneous arrangement and no coarse grains are visible. This homogeneity test was carried out before and during cycling test 10,11,12 .…”
Section: Homogeneity Testmentioning
confidence: 99%